Pengembangan E-LKPD Berbasis Open Ended Problem Tema Pemanasan Global Untuk Melatih Kemampuan Berpikir Kreatif Siswa Kelas VII - Shafira Putri Andini; Suroso Mukti Leksono; Mudmainah Vitasari (PendIPA Journal of Science Education, 2022)
Learning activities that lead to creative thinking skills have not been fully implemented.. Creative thinking skills can be trained by developing teaching materials in the form of E-Worksheet which is able to train students' reasoning abilities. The open-ended problem approach is able to direct students to solve problems in various ways. So that the E-Worksheet based on open ended problems is able to give students the freedom to describe the results of creative analysis to solve problems. The purpose of this study is to measure the level of validity of the E-Worksheet based on the open ended problem of the global warming theme to train the creative thinking skills of grade VII students. The method used is research and development or Research and Development (R&D) with the 4D research and development model by Thiagarajan (1975) which is modified as needed by being limited to the development stage until the product validation test. The instrument used is a validation questionnaire sheet that has been tested by instrument experts to determine the level of validity of the developed E-Worksheet. Data were analyzed descriptively quantitatively and qualitatively. The results showed that the level of validity of the E-LKPD based on the open ended problem of the global warming theme obtained a value of 89,1% with the "very valid" category. The results of the assessment are based on the average value of material experts, media experts, and expert practitioners.